The Accuracy and the Acceptability of Ten Popular Indonesian Songs Translation from Indonesian into English - Kumandang Kidung Puja Pamarta (Institute of Research and Community Outreach - Petra Christian University, 2022)
Songs are short piece of music with word that are sung (Cambridge Dictionary) or in Bahasa Indonesia we can call it